A Modular and Extensible Framework for Human Resource System - Muhammad Zabir Abdul Halim; Marshima Mohd Rosli (Institute of Advanced Engineering and Science, 2018)
Human Resource is an essential part for an organization and integration of technology would just enhance the effectiveness. One of the scope that Human Resource must take note is performance and productivity. However, there is still no infallible or highly reliable way to measure productivity and performance of an organization and its employees for current industrial Human Resource systems. There is still possible improvement that can be made to the system in the current time. The purpose of this study is to propose a modular and extensible framework of Human Resource systems that used to measure the performance and productivity of an organization. This study compares the different criteria of existing Human Resource systems to ensure the proposed framework would surpassed the current real world industrial system. The results of the review provide insights for important criteria in HR system to increase the accuracy of the performance review. This study also constructs Entity Relationship Diagram (ERD) to demonstrate the logical structure of the proposed framework. The ERD will form the foundation of the proposed framework to improve the Human Resource system for evaluating the productivity and performance of an organization.